Do Negatively Framed Messages Motivate Political Participation? Evidence From Four Field Experiments. Issue 1 (January 2020) - Mann, Christopher B.; Arceneaux, Kevin; Nickerson, David W.
A multitude of laboratory experiments show that subtle shifts in framing can induce individuals to participate in political activity. Using four randomized field experiments, we tested whether exposure to messages framing public policy proposals negatively increased political action relative to exposure to messages framing the proposal positively. Three experiments use a type of political participation novel to the field experiments literature: phone calls recruiting people to contact elected officials. Contrary to expectations from prior laboratory experiments on intention to participate in collective action in politics, we find scant evidence that messages framed negatively about the policy returns from participation are more effective than messages framed positively about the policy returns from participation at motivating real-world political behavior.